2021
DOI: 10.1002/anie.202100071
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Constructed Silver Active Sites in Gold Nanoclusters for Chemical Fixation of CO2

Abstract: Precise control of the composition and structure of active sites in an atom‐by‐atom fashion remains insuperable for heterogeneous catalysts. Here, we introduce tailor‐made catalytic sites for the cycloaddition of CO2 to epoxides achieved by implementing Ag atoms at different levels of liberation in atomically precise Au nanoclusters. Our results reveal that a single open Ag site on the Au19Ag4 cluster improves the ring‐opening of epoxides and sequent CO2 insertion, while the partially exposed Ag site on the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 26 publications
1
72
0
Order By: Relevance
“…It was reported that the conversion of epoxides into cyclic carbonates could be effectively improved by increasing the reaction temperature and pressure or prolonging the reaction time. [44][45][46][47] Indeed, although carried out under room temperature and 1 atm pressure, the yields of propylene carbonate and 1,2butylene carbonate by PTC-285 could still be increased to 99% and 95% by prolonging the reaction time to 48 hours (Table 3, entry 1, 3). In addition, the size effect of the substrate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the conversion of epoxides into cyclic carbonates could be effectively improved by increasing the reaction temperature and pressure or prolonging the reaction time. [44][45][46][47] Indeed, although carried out under room temperature and 1 atm pressure, the yields of propylene carbonate and 1,2butylene carbonate by PTC-285 could still be increased to 99% and 95% by prolonging the reaction time to 48 hours (Table 3, entry 1, 3). In addition, the size effect of the substrate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum-sized metal nanoclusters, which bridge the gap between organometallics and nanocrystals, exhibit dramatically unique electronic and optical properties, such as molecule-like energy gaps (Schaaff et al, 1997;Lee et al, 2004;Negishi et al, 2005;Walter et al, 2008;Zhu et al, 2008;Russier-Antoine et al, 2014;Bertorelle et al, 2017;Chakraborty and Pradeep, 2017), intense photoluminescence (Zheng et al, 2004;Zheng et al, 2007;Xie et al, 2009;Luo et al, 2012;Musnier et al, 2019) and catalytic properties (Tsunoyama et al, 2009;Zhu et al, 2010;Li et al, 2016a;Cai et al, 2019;Lv et al, 2019;Lv et al, 2020a;Yang et al, 2020a;Lv et al, 2020b;Cai et al, 2020;Li et al, 2021). Luminescent thiolated-protected Au and Ag NCs in particular have attracted tremendous interest due to their wide applications in bio-imaging, bio-medicine, sensing, and catalysis (Jin, 2010;Díez and Ras, 2011;Bonacic-Koutecky et al, 2012;Zheng et al, 2012;Luo et al, 2014;Sun and Jin, 2014;Jin et al, 2016;Lei et al, 2018;Yan et al, 2018;Ungor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of incorporating different heterometals into gold NCs [3, 6–10] . These bimetallic NCs are also applied in bio‐sensing and catalysis with significantly enhanced functionalities [2, 11–17] …”
Section: Figurementioning
confidence: 99%
“…[3,[6][7][8][9][10] These bimetallic NCs are also applied in bio-sensing and catalysis with significantly enhanced functionalities. [2,[11][12][13][14][15][16][17] In thiolate-protected gold-based bimetallic NCs, a general trend of the distribution of metal elements is that the surface is typically composed of the less noble metal with low valence state, such as Ag I and Cu I , resembling Au I in homo gold NCs. [8,18,19] Heterometals with high valence state (II or higher), such as Cd, can be doped into the sub-surface (beneath the staple motifs) of thiolated gold NCs but only with a limited number of Cd atoms (e.g.…”
mentioning
confidence: 99%